Bar charts of false positive misclassifications for tested clinicopathologic findings across all testers. - Stefan Saverimuttu (20882325) (2025)
Number of false positive accessions extracted (y-axis) by each anonymised tester (x-axis) stacked by reason for misclassification (key), for each tested clinicopathologic finding (as labelled) during pilot testing of the application, DEE, for extraction of necropsy data from the Wildbase Pathology Register.